In Vivo Platelet Kinetics in 31 Diabetic Patients - Dassin, E; Najean, Y; Poirier, O; Passa, Ph; Bensoussan, D (Thrombosis and Haemostasis, 1978)
In vivo platelet survival was estimated, in 31 diabetic patients, using 51Cr-labelled autologous platelets. A mathematical analysis attempted to measure the “potential” life span (senescence process) and the degree of a superimposed aleatory destruction (consumption process).The potential platelet life span in diabetics did not differ from normal values. However, excessive consumption was observed in one third of the studied cases, without correlation with the age of the patients, the clinical duration of diabetes, and the degree of vascular impairment. Thus, platelet kinetic studies did not provide presently useful indications, in a particular patient, regarding the prognosis of the vascular disease, and the justification of anti-aggregant therapy.